2003
DOI: 10.1088/0029-5515/43/3/303
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of neo-classical tearing modes by mode coupling

Abstract: The formation of magnetic islands with mode numbers (m>1,n=1) apparently triggered by sawtooth crashes has for a long time been a concern in JET discharges with auxiliary heating as it affects the peak performance, in terms of stored energy or of neutron yield (in DT experiments). The phenomenological association of the sawtooth crash with the onset of resistive modes is becoming particularly relevant in the context of Neoclassical Tearing Modes (NTM) theory that requires the formation of a "seed" island above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…In addition to the sawtooth instability, other MHD modes are expected to act on the tungsten transport [Nave 2003, Pütterich 2013, Angioni 2014. When the large sawtooth (∆Te=1.5keV) occurs after the 1.3s long sawtooth free period (#85376), a (m=3, n=2) neoclassical tearing mode (NTM) is destabilized for the rest of the discharge (f=9-10kHz) whereas a m=1, n=1 internal kink mode (f=8-9kHz) is present during the other pulses (#85377 &85081).…”
Section: Figure 4 A) Central Electron Temperature B) Normalized Densimentioning
confidence: 99%
“…In addition to the sawtooth instability, other MHD modes are expected to act on the tungsten transport [Nave 2003, Pütterich 2013, Angioni 2014. When the large sawtooth (∆Te=1.5keV) occurs after the 1.3s long sawtooth free period (#85376), a (m=3, n=2) neoclassical tearing mode (NTM) is destabilized for the rest of the discharge (f=9-10kHz) whereas a m=1, n=1 internal kink mode (f=8-9kHz) is present during the other pulses (#85377 &85081).…”
Section: Figure 4 A) Central Electron Temperature B) Normalized Densimentioning
confidence: 99%
“…In other words, the triggering of NTMs in a device is not directly linked to the b levels but to the mechanisms which generate seed islands. 4 Previous research has identified several different causes for the formation of seed islands such as an unstable tearing mode, [5][6][7] MHD events such as sawtooth 8 and fishbones, 9 error fields, 10,11 edge localized modes (ELMS), 12 nonlinear mode coupling, 13 and turbulence. 14,15 This diversity of origins poses serious challenges for experimentally anticipating their appearance and choosing appropriate control parameters for their avoidance and suppression.…”
Section: Introductionmentioning
confidence: 99%
“…11 For all our runs, we have ensured that this happens by keeping the ratio to be ! 10 6 . Finally, Equation (4) is the evolution equation for the parallel velocity component.…”
Section: Model Equationsmentioning
confidence: 99%
“…NTMs are believed to set the upper limit on attainable normalized plasma b N 3,4 in long pulse tokamaks and have therefore been the subject of much experimental and theoretical investigations in the recent past. [5][6][7][8][9][10][11] While there has been considerable progress in the experimental characterization and control of this instability with concurrent development of a useful theoretical framework in the form of a model island evolution equation (the modified Rutherford equation) there are still many basic physics issues associated with the mode that remain poorly understood or relatively less explored. The trigger and the mechanism for the creation of the seed island, nonlinear mode coupling between NTMs of different helicities, interaction of the magnetic island with energetic particles, evolution of the island in a turbulent media [12][13][14] are among some of the basic areas that need further attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation